Is ADHD a Risk Factor for High School Dropout? A Controlled Study. (May 2016) - Fried, Ronna; Petty, Carter; Faraone, Stephen V.; Hyder, Laran L.; Day, Helen; Biederman, Joseph
Objective: This study examined whether ADHD was an independent contributor to grade retention when adjusting for IQ, learning disorders, and social class.Method: Outcome data was from participants in studies at Massachusetts General Hospital ( n = 404 ADHD, n = 349 controls) who underwent psychiatric interviews, socioeconomic status measures, and IQ testing.Results: 28% of individuals with ADHD repeated a grade compared with 7% of controls ( p < .001). Among participants with ADHD, social class, and IQ were significant predictors of high school dropout or repeated grade. An interaction effect of ADHD and gender was also found with females with ADHD having a higher risk ratio for repeated grade/dropout compared with males with ADHD.Conclusion: Participants with ADHD were significantly more likely to repeat a grade, adjusting for all other variables indicating the critical importance of early identification of ADHD to help mitigate adverse educational outcomes. (J. of Att. Dis. 2016; 20(5) 383-389)